Educação à distância: um desafio estratégico para as instituições de ensino superior – um estudo de caso - Freitas, Soraya Maria de Oliveira (2009)
The search for knowledge and professional skills have become fundamental to competition and integration in the labor market. Because of this, there was growth of Distance Education (EAD) in higher education institutions to meet people who, for some reason, they had chances to acquire higher education, become better prepared to face the job market. The research deals with distance learning and aims to examine whether it is strategic to their deployment in IES, both for students and for educational institutions. It is concluded that despite high growth in the world and Brazil are required restatements of certain strategies for Distance Education does not lose the quality of teaching, thus making it interesting for everyone involved.